KENEGARAWAN KEPEMIMPINAN PARTAI POLITIK GUNA MEWUJUDKAN KONSOLIDASI POLITIK PASCA PEMILU 2019 - Ridwan Ridwan (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
The 2019 simultaneous elections with all their dynamics have the potential for conflict because the community is divided on their respective choices. The KPU became gossip in the community with the appearance of news of an alleged miscalculation of the general election results. This shows the magnitude and spread of potential conflicts in the 2019 elections. Problems faced by political party leaders post-election with very tight competition in the form of a crisis of trust, conflicts of interest, lack of synergy between national leaders due to sectoral ego, regional autonomy, and multi-ethnic, multi-ethnic religion, and multi-culturalism, as well as the erosion of local wisdom values. The political awareness of the Indonesian people is still relatively low and there are even politically illiterate people who are easily provoked so that the leadership of political parties is required to have a statesman character.